Treatment of Phlegmon of the Maxillofacial Area by Activation of Nonspecific Immune Factors Using a Bacteriophage - Qayimovich, Rakhimov Zokir (Miasto Przyszłości, 2023)
The use of complex treatment, which included Bacteriophage, had an anti-inflammatory, immunomodulatory, and therapeutic effect. The bacteriophage effectively eliminated disturbances in the system of nonspecific immunological resistance, it also had a regenerative and reparative effect in patients with diffuse odontogenic phlegmon of the maxilla fasial area. The patients were divided into 2 groups. The results of the two treatments are compared. Traditional treatment did not lead to positive dynamics of the main parameters of nonspecific immunological protection in patients with diffuse odontogenic phlegmon of the maxilla facial area.